The taxonomy of the subtribe aveninae excluding helictotrichon schult Part 1 & 2 - Sokutu, Tamsanqa Mthunzi (Department of Biological Sciences, 2024)
The sub-tribe Aveninae Presl in southern Africa is represented.by nine genera, eight of which are included in this study. Most of these genera have been introduced from elsewhere, in most cases from Europe. A morphological and anatomical account of this subtribe excluding Helictotrichon Schult. is given and keys to genera and species are also provided. Characters that are employed in Flora guropaea to differentiate between genera and species have, with few exceptions been fotinci to be useful.